Using Innovation Techniques to Generate ‘New’ Problems - Vistro-Yu, Catherine P (Archīum Ateneo, 2009)
Teachers sometimes run out of ideas and have difficulty creating new problems for our students to solve. When those times come, the remedy is to innovate on existing and old problems that have proven to be useful and effective in teaching mathematical skills. In this paper, the author gives some pointers on how to innovate on “used” problems with the objective of developing “new” problems to give to students. The technique is a borrowed concept from literature and is applied to mathematical problem solving, particularly, problem generation or problem formulation.